Patellar tendon adaptations to resistance training in young women using combined oral contraceptives - Vesterhus, Ingvild; Hesseberg, Eirik R.; Fjeldberg, Ken; Engstad, Martin K.; Paulsen, Gøran; Hansen, Mette; Nordez, Antoine; Lacourpaille, Lilian; Seynnes, Olivier R. (PeerJ, 2025)
Background The study aimed to examine the impact of combined oral contraceptive pill (OC) use on patellar tendon (PT) adaptation to resistance training in young women. Methods Fifteen users of OC (28 ± 3 years) (OC group) and 17 eumenorrheic non-users (32 ± 5 years) (NOC group) performed heavy resistance training of the knee extensors over a period equivalent to three menstrual or pill cycles. Maximal isometric strength of the knee extensor muscles, PT cross-sectional area (CSA), tensile stiffness, and shear wave velocity (SWV) were measured before and after the intervention using combined ultrasonography and dynamometry. Results The training period increased maximal isometric strength in both groups (≈11%, P < 0.001) with no significant interaction with OC use (p = 0.965). Likewise, a small yet significant increase in proximal tendon CSA was observed (1.5 ± 1.6% for both groups, main training effect P < 0.001) without any significant interaction with OC use (p = 0.267). Tendon tensile stiffness also increased significantly (18.9 ± 26.3% in the OC group and 28.2 ± 35.1% in the NOC group, main effect: P < 0.001) but was not significantly affected by OC use (interaction effect: p = 0.428). Tendon SWV measurements yielded similar results, indicating a main effect of training (+12% on average, p = 0.024) but no significant interaction with OC use. Conclusion These findings suggest that OC use does not affect the increase in PT CSA and mechanical properties following short-term resistance training in young untrained females.
Keywords: Oestrogen; Tendon hypertrophy; Tendon stiffness; Hormonal influence